Universal Plug and Play Machine Models - Glässer, U.; Gurevich, Y.; Veanes, M.; Gurevich, Yuri; Veanes, Margus (2001)
Recently, Microsoft took a lead in the development of a standard for peer-to-peer network connectivity of various intelligent appliances, wireless devices and PCs. It is called the Universal Plug and Play Device Architecture (UPnP). We construct a high-level Abstract State Machine (ASM) model for UPnP. The model is based on the ASM paradigm for distributed systems with real-time constraints and is executable in principle. For practical execution, we use AsmL, the Abstract state machine Language, developed at Microsoft Research and integrated with Visual Studio and COM. This gives us an AsmL model, a refined version of the ASM model. The third part of this project is a graphical user interface by means of which the runs of the AsmL model are controlled and inspected at various levels of detail as required for e.g. simulation and conformance testing.